2010
DOI: 10.1111/j.1460-9568.2010.07352.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of DNAJB family members (HSP40) correlate with disease onset in patients with spinocerebellar ataxia type 3

Abstract: In polyglutamine disorders, the length of the expanded CAG repeat shows a strong inverse correlation with the age at disease onset, yet up to 50% of the variation in age of onset is determined by other additional factors. Here, we investigated whether variations in the expression of heat shock proteins (HSP) are related to differences in the age of onset in patients with spinocerebellar ataxia (SCA)3. Hereto, we analysed the protein expression levels of HSPA1A (HSP70), HSPA8 (HSC70), DNAJB (HSP40) and HSPB1 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…In HEK 293T cells, DnaJB1 is moderately expressed and is highly inducible upon heat stress (Hageman et al, 2010;Hageman et al, 2011). It has been shown that DnaJB1 suppresses the aggregation of polyQ proteins (Rujano et al, 2007;Zijlstra et al, 2010) and also prevents luciferase aggregation during heat stress (Hageman et al, 2010). Moreover, it has been demonstrated that overexpression of Hsp70 and DnaJB1 facilitates the degradation of polyQ expanded forms of the androgen receptor (Bailey et al, 2002).…”
Section: Vi8 Role Of Dnajb1 In the Degradation Of Proteinsmentioning
confidence: 99%
“…In HEK 293T cells, DnaJB1 is moderately expressed and is highly inducible upon heat stress (Hageman et al, 2010;Hageman et al, 2011). It has been shown that DnaJB1 suppresses the aggregation of polyQ proteins (Rujano et al, 2007;Zijlstra et al, 2010) and also prevents luciferase aggregation during heat stress (Hageman et al, 2010). Moreover, it has been demonstrated that overexpression of Hsp70 and DnaJB1 facilitates the degradation of polyQ expanded forms of the androgen receptor (Bailey et al, 2002).…”
Section: Vi8 Role Of Dnajb1 In the Degradation Of Proteinsmentioning
confidence: 99%
“…A large body of evidence has established that AO is not entirely explained by CAGexp, which explains 50% to 60% of the variability in AO,5–8 and that AO should be modulated by additional genetic and/or environmental factors. Several candidates have been proposed, such as apolipoprotein E genotypic status,9–11 CAG length at normal ATXN3 8 12 13 and ATXN2 6 8 alleles, and protein levels of the DNAJB1 chaperone 14…”
Section: Introductionmentioning
confidence: 99%
“…For example, TR copy number mutations that expand polyglutamine (polyQ) tracts past a threshold number of glutamines can cause incurable neurodegenerative diseases, such as Huntington disease and Spinocerebellar Ataxias (2,3). PolyQ tract length correlates with onset and severity of polyQ expansion disorders, but for intermediate polyQ tracts this correlation is far weaker (4)(5)(6)(7)(8), suggesting that genetic and environmental modifiers exist (9)(10)(11)(12). Despite their potential for pathogenicity, variable polyQ tracts occur frequently in eukaryotic proteins, many of them functioning in development and transcription (1,(13)(14)(15).…”
mentioning
confidence: 99%